Athlete muscular phenotypes identified and compared with high-dimensional clustering of lower limb muscle volume measurements - Knaus, K. R.; Handsfield, G. G.; Fiorentino, N. M.; Hart, J. M.; Meyer, C. H.; Blemker, S. S. (Medicine & Science in Sports & Exercise, 2023)
Introduction Athletes use their skeletal muscles to demonstrate performance. Muscle force generating capacity is correlated with volume, meaning that variations in sizes of different muscles may be indicative of how athletes meet different demands in their sports. Medical imaging enables in vivo quantification of muscle volumes; however, muscle volume distribution has not been compared across athletes of different sports.